Dynamics of receptor-operated Ca2+ currents through TRPC channels controlled via the PI(4,5)P2-PLC signaling pathway - Mori, Masayuki X.; Itsuki, Kyohei; Hase, Hideharu; Sawamura, Seishiro; Kurokawa, Tatsuki; Mori, Yasuo; Inoue, Ryuji (Frontiers in Pharmacology, 2015)
Transient receptor potential canonical (TRPC) channels are Ca2+-permeable, nonselective cation channels that carry receptor-operated Ca2+ currents (ROCs) triggered by receptor-induced, phospholipase C (PLC)-catalyzed hydrolysis of phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2). Within the vasculature, TRPC channel ROCs contribute to smooth muscle cell depolarization, vasoconstriction and vascular remodeling. However, TRPC channel ROCs exhibit a variable response to receptor-stimulation, and the regulatory mechanisms governing TRPC channel activity remain obscure. The variability of ROCs may be explained by their complex regulation by PI(4,5)P2 and its metabolites, which differentially affect TRPC channel activity. To resolve the complex regulation of ROCs, the use of voltage-sensing phosphoinositide phosphatases and model simulation have helped to reveal the time-dependent contribution of PI(4,5)P2 and the possible role of PI(4,5)P2 in the regulation of ROCs. These approaches may provide unprecedented insight into the dynamics of PI(4,5)P2 regulation of TRPC channels and the fundamental mechanisms underlying transmembrane ion flow. Within that context, we summarize the regulation of TRPC channels and their coupling to receptor-mediated signaling, as well as the application of voltage-sensing phosphoinositide phosphatases to this research. We also discuss the controversial bidirectional effects of PI(4,5)P2 using a model simulation that could explain the complicated effects of PI(4,5)P2 on different ROCs.